The role of oil in Russia’s economy - M. M. Solovyev (Путеводитель предпринимателя, 2020)
The article is considered the role and contribution of the oil sector in key macroeconomic, government budget, foreign trade and investment indicators, It has been determined the full value-added of oil sector and carried out the comparative analysis of the main world oil market players and Russian oil companies.